Proceedings of the Twenty-Eighth Annual ACM-SIAM Symposium on Discrete Algorithms 2017
DOI: 10.1137/1.9781611974782.88
|View full text |Cite
|
Sign up to set email alerts
|

Hardness of Continuous Local Search: Query Complexity and Cryptographic Lower Bounds

Abstract: Local search proved to be an extremely useful tool when facing hard optimization problems (e.g., via the simplex algorithm, simulated annealing, or genetic algorithms). Although powerful, it has its limitations: there are functions for which exponentially many queries are needed to find a local optimum. In many contexts the optimization problem is defined by a continuous function, which might offer an advantage when performing the local search. This leads us to study the following natural question: How hard is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Furthermore, they show that two well-known problems in CLS, the P-Matrix Linear Complementarity Problem (P-LCP), and finding a fixpoint of a piecewise-linear contraction map (PL-Contraction) belong to the class. The End of Potential Line problem of [27] is closely related to the End of Metered Line of [39].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they show that two well-known problems in CLS, the P-Matrix Linear Complementarity Problem (P-LCP), and finding a fixpoint of a piecewise-linear contraction map (PL-Contraction) belong to the class. The End of Potential Line problem of [27] is closely related to the End of Metered Line of [39].…”
Section: Introductionmentioning
confidence: 99%
“…See Section 3 for details. We remark that related constructions were known for two dimensions [Vav93,HY17,BM20,CDHS20].…”
Section: The Potential Functionmentioning
confidence: 97%
“…6 For our construction, we essentially use the End-of-Metered-Line [HY17,FGMS19] variant of the problem, which also encodes a potential function on the line.…”
Section: Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…This was generalized in [Jer16] by proving that the problem of factoring integers is in PPA ∩ PPP under randomized reductions. Recently, strong cryptographic assumptions were used to prove the average-case hardness of PPAD and CLS [BPR15, GPS16,HY17]. In [RSS17] it was shown that average-case PPAD hardness does not imply one-way function under black-box reductions, whereas in [HNY17] it was shown that any hard on average problem in NP implies the average case hardness of TFNP.…”
Section: Related Workmentioning
confidence: 99%